Microwave Plasmas at Atmospheric Pressure. Issue 1 (5th November 2013) - Leins, M.; Kopecki, J.; Gaiser, S.; Schulz, A.; Walker, M.; Schumacher, U.; Stroth, U.; Hirth, T.
Abstract Microwave plasmas at atmospheric pressure are used for surface treatments like for example cleaning, sterilization or decontamination purposes, for a pre‐treatment to increase the adhesion of lacquer, paint, or glue, and for the deposition of different kind of layers and coatings. Micro plasma jets can also be applied for biomedical applications and for treatment of small and complex geometries like for example the inside of capillaries. Larger plasma torches which exhibit higher gas temperatures can also be used for chemical syntheses like waste gas decomposition, methane pyrolysis, or carbon dioxide dissociation and for plasma spraying purposes. In the present publication an overview on the development and the investigation of the operating principle of two atmospheric pressure microwave plasma torches at frequencies of 2.45 GHz and 915 MHz will be presented. The plasma sources are based on a cylindrical resonator combined with coaxial structures. To explain how these plasma sources work, simulations of the electric field distribution will be discussed. Furthermore, some physical characteristics of an air and an Ar/H2 atmospheric plasma like gas temperatures, excitation temperatures and densities as well as the heating of the plasma by the microwave will be investigated. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)